Implikasi Hukum Perdagangan Internasional terhadap Kebijakan Biodiesel B50 atas Komoditas Minyak Sawit Indonesia - Jumantoro, Tegar Raffi Putra; Kusuma, Ajeng Pramesthy Hardiani; Hasan, Nurhaedah; Kairuddin, Kairuddin (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2026)
Indonesia's B50 biodiesel policy creates a legal dilemma between national energy policy sovereignty and international trade obligations under the WTO system. This research analyzes the legal implications of the B50 policy, which impacts the reduction of CPO export volumes and triggers allegations of protectionism from trading partners, particularly the European Union. Through a normative juridical approach employing statutory, conceptual, and comparative methods, this study examines the consistency of national regulations with WTO principles such as most favoured nation (MFN), national treatment, and transparency, while evaluating the legal justification space through development space principles and General Exceptions (Article XX GATT). A comparative study of Argentina's and Brazil's experiences in biodiesel disputes at the WTO reveals two different strategies: litigation based on technical documentation and diplomatic approaches with sustainable development narratives. This research finds that Indonesia has legal justification space for the B50 policy, but requires strengthened normative arguments, policy transparency, and technical document preparedness to anticipate potential disputes. These findings provide strategic contributions to formulating Indonesia's legal position in multilateral forums through the establishment of cross-sectoral task forces, strengthening policy narratives based on global justice, and optimizing international legal cooperation so that the B50 policy obtains both legal and international legitimacy.